STOCK ANALYSIS OF MAP AKTIF ADIPERKASA USING FUNDAMENTAL ANALYSIS WITH INDONESIA AFTER PANDEMIC PROJECTION (The Indonesian Journal of Business Administration, 2021)
MAP Aktif Adiperkasa (MAPA) is a company engaged in the retail industry that sells various consumer needs products related to healthy lifestyle, MAPA is a subsidiary of Mitra Adiperkasa (MAPI) which manages sales in the sports equipment products sector. MAPA has special distribution rights for some of the flagship products such as Nike, Adidas, Reebok etc, MAPA outlets can be found in various public shopping places in Indonesia. In 2020 the Covid-19 pandemic entered Indonesia which caused the government to impose several regulations aimed at preventing the spread of the Covid-19 virus, one of which is a large-scale social restriction requiring shopping centers that result in crowds having to be closed or should not be operational. This study uses PEST analysis for macro analysis, for industry analysis using 5 force porters. For internal analysis only use financial analysis by comparing the ratio of financial ratios between MAPA and MAPI. To obtain fair value from MAPA shares using discounted cash flow and relative valuation with EBITDA, with WACC of 16.68% and using Indonesia's projected economic growth during the period of improvement after the pandemic, obtained fair value by DCF method of Rp.1.011,59. With this result, it is concluded that for now investors who own MAPA shares are advised to sell their shares and re-enter at a time when MAPA stock market price has touched its fair price. Keywords: MAPA, Stock, Pandemic, Covid-19, DCF, WACC, EBITDA